2002
DOI: 10.1182/blood-2002-01-0087
|View full text |Cite
|
Sign up to set email alerts
|

High-dose cyclophosphamide for refractory autoimmune hemolytic anemia

Abstract: High-dose cyclophosphamide, without stem cell rescue, has been used successfully to treat aplastic anemia and other autoimmune disorders. To determine the safety and efficacy of high-dose cyclophosphamide among patients with severe refractory autoimmune hemolytic anemia, we treated 9 patients with cyclophosphamide (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 15 publications
2
55
0
6
Order By: Relevance
“…High-dose cyclophosphamide is a highly immunosuppressive agent that, in addition to its successful use as a treatment for aplastic anemia [9][10][11] and other severe refractory autoimmune diseases, 14,16,21,22 has proven efficacy in allogeneic BMT as both a conditioning regimen 23 and graft-versus-host disease prophylaxis. 24 Cyclophosphamide's unique metabolism is responsible for its immunosuppressive yet stem cell-sparing properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-dose cyclophosphamide is a highly immunosuppressive agent that, in addition to its successful use as a treatment for aplastic anemia [9][10][11] and other severe refractory autoimmune diseases, 14,16,21,22 has proven efficacy in allogeneic BMT as both a conditioning regimen 23 and graft-versus-host disease prophylaxis. 24 Cyclophosphamide's unique metabolism is responsible for its immunosuppressive yet stem cell-sparing properties.…”
Section: Discussionmentioning
confidence: 99%
“…High-dose cyclophosphamide is highly immunosuppressive and has been used to successfully treat SAA [9][10][11][12][13] and other severe autoimmune diseases [14][15][16][17] in several small trials. A pilot study of 10 patients treated with high-dose cyclophosphamide demonstrated that this approach has the potential to cure SAA; 6 of these patients had between 9 and 19 years of follow-up at the time of publication in 1996, 9 and all 6 remain alive and disease free with normal blood counts out 21 to 31 years from initial therapy (R.A.B.…”
Section: Introductionmentioning
confidence: 99%
“…67 Alemtuzumab, a humanized anti-CD52 monoclonal antibody, has been shown to be effective in small series of patients with idiopathic refractory AIHA, with an overall complete remission rate in 13 of 16, including 3 pediatric cases. 23,68,69 However, because of the high toxicity, it is considered a "last resort" option in severe idiopathic AIHA unresponsive to all previous treatments.…”
Section: "Last Option" Treatmentsmentioning
confidence: 99%
“…Por esta razão, além do Brasil (14)(15)(16)(17)(18)(21)(22) e da China (16,(38)(39)(40) , incluindo Hong-Kong (41) , outros países emergentes, como a Rússia (42) , a Hungria (43) , a Coréia do Sul (44) , a República Tcheca (45) e a Grécia (46) têm se dedicado crescentemente ao TCTH em DAI. Uma outra questão de grande importância nesta área, e ainda bastante controversa, se refere ao mecanismo de ação do transplante das células-tronco hematopoéticas nas DAI e o papel das CTH (n. o 1, Tabela 2). No transplante autó-logo, existem três explicações possíveis para este mecanismo de ação (47) : 1) efeito isolado da imunossupressão em altas doses na eliminação de linfócitos auto-reativos; neste caso, as CTH deveriam apenas prover suporte hematopoético após a imunossupressão em altas doses, reduzindo o período de pancitopenia pós-transplante; 2) as CTH poderiam restaurar a auto-tolerância a tecidos próprios, perdida na emergência DAI; ou 3) as CTH poderiam promover reparação tecidual por meio de transdiferenciação das CTH ou outras CT em células do tecido lesado pela DAI. A primeira hipótese é suportada pelo benefício clínico observado em pacientes submetidos a imunossupressão em altas doses (200 mg/kg de ciclofosfamida endovenosa) sem resgate com CTH (48)(49)(50) . Nesses pacientes, o tempo de pancitopenia foi superior ao observado quando se usa resgate de CTH (14-17 dias vs. 8-10 dias) e não ocorreram recaídas após um seguimento médio de 29 meses para LES, 15 meses para anemia hemolítica auto-imune e de 6 meses a 6 anos para miastenia gravis.…”
Section: Possíveis Respostas Estratégias De Investigação Referênciaunclassified
“…Entretanto, os marcadores celulares mais eficientes conhecidos, retrovirais, dificilmente terão seu uso permitido a curto prazo, em razão de recentes acidentes ocorridos em protocolos de terapia gênica (60) . Uma forma indireta e mais limitada de se estudar o efeito das células-tronco hematopoéticas na terapia das DAI seria por meio de protocolos randomizados comparando o TCTH com a imunossupressão em altas doses isoladas, sem infusão de CTH (48)(49)(50) . Esses estudos, entretanto, são difíceis de realizar em razão do período prolongado de neutropenia a que seria submetido o grupo controle (sem resgate hematopoético).…”
Section: Possíveis Respostas Estratégias De Investigação Referênciaunclassified